Analisis Pandangn Fikih Siasah Terhadap Tindakan Terorisme: Implikasi Terhadap Keamanan Dan Keadilan Sosial - Mitra Atllah Syahputra; Askana Fikriana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore the views of Fikih Siasah on acts of terrorism within the context of Islam and their implications for security and social justice. In pursuit of this goal, we employ a literature review methodology as our research framework. The analysis results indicate that a profound understanding of acts of terrorism and efforts to address their consequences is essential. Terrorism often poses threats to societal security and affects the principles of social justice. To create a safer and more just society, cooperation among nations, the international community, and individuals is required. This abstract reflects the urgency and relevance of the topic in the constantly evolving global landscape and emphasizes the importance of global collaboration in addressing this challenge.